PENGEMBANGAN MEDIA VIDEO PEMBELAJARAN UNTUK MENINGKATKAN KEMAMPUAN NUMERASI SISWA DI SEKOLAH DASAR - Nurhayati; Abdul Haling, Dedy Aswan (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study was conducted by researchers referring to initial observations where researchers found the fact that the teaching module used was not in accordance with the guidelines for implementing the independent curriculum, where data that was designed visually still required data in the form of clear images or illustrations and materials that were not yet appropriate, especially in sociology subjects. This study aims to (1) determine the level of development needs, (2) design sociology subject teaching modules, (3) determine the level of validation of teaching modules, (4) determine the level of practicality of teaching modules. This study uses an R&D approach with the ADDIE development model (analysis, design, development, implementation, evaluation). Data collection techniques use questionnaires and documentation. This study was conducted at SMA Negeri 3 Luwu Timur with a total of 30 students and 1 sociology subject teacher as research subjects. The results of this study indicate that the needs analysis is at the level of need, needed because the previous teaching devices were not optimal, which were dominated by printed books, so that interactive teaching modules were needed and contained reading materials, videos and evaluation instruments. Then in the design of the teaching module developed using software such as Microsoft Word, Canva, Capcut and hardware using a printer. The level of product validity based on the alpha test of learning media experts is in a very valid qualification, then the material/content experts are in a very valid qualification so that it can be tested in the field. The level of product practicality is in a very practical qualification and the teacher's response results are in a very practical qualification. Based on the results of research and development, this teaching module is able to increase student involvement and understanding in accordance with the principles of the independent curriculum and can be an innovative alternative in supporting the learning process.